Basidiomycete (Pseudolagarobasidium acaciicola) in coconut (Cocos nucifera) suspension culture — a report (Current Horticulture, 2024)
Coconut (Cocos nucifera L.), a monospecific woody tree is recalcitrant to in-vitro culture. Doubling the yield through technological interventionshas been reported in many palm species (Manorama et al., 2019). Even though most of the in-vitro protocols use solid media, suspension cultures utilizing liquid media for establishing embryogenic cells with high regenerative capacity is reported (Al-Khayri, 2012). As the liquid media provide uniform conditions of nutrient availability to explants, mass multiplication of coconut embryogenic cells from plumular explant via suspension culture was attempted.